Iowa gambling task impairment in Parkinson's disease can be normalised by reduction of dopaminergic medication after subthalamic stimulation. Issue 2 (23rd May 2014) - Castrioto, Anna; Funkiewiez, Aurélie; Debû, Bettina; Cools, Roshan; Lhommée, Eugénie; Ardouin, Claire; Fraix, Valérie; Chabardès, Stephan; Robbins, Trevor W; Pollak, Pierre; Krack, Paul
Abstract : Background: Impulse control disorders (ICD), including pathological gambling, are common in Parkinson's disease (PD) and tend to improve after subthalamic (STN) stimulation after a marked reduction of dopaminergic medication. In order to investigate the effect of STN stimulation on impulsive decision making, we used the Iowa Gambling task (IGT). Methods: We investigated IGT performance in 20 patients with PD before STN surgery with and without dopaminergic treatment and in 24 age-matched controls. All patients underwent an extensive neuropsychological interview screening for behavioural disorders. Assessment in patients was repeated 3 months after surgery without dopaminergic treatment with and without stimulation. Results: Chronic antiparkinsonian treatment was drastically reduced after surgery (−74%). At baseline, on high chronic dopaminergic treatment 8/20 patients with PD presented with pathological hyperdopaminergic behaviours, which had resolved in 7/8 patients 3 months after surgery on low chronic dopaminergic treatment. Preoperative performance on the IGT was significantly impaired compared to after surgery. Conclusions: Dopaminergic medication likely contributes to the impairment in decision making underlying ICDs. Deep brain stimulation allows drastic reduction of dopaminergic medication and, thus, concomitant remediation of medication-induced impairment in decision making.